High-grade cervical leiomyosarcoma: a case report - Rosas Ortega, Pricilla Iliana; Beltrán Serrano, Erik; Leal Chigo, Miguel Angel; Bermudez Ruiz, Judith Del Rosario; Vazquez Sánchez, Victor Adrian; Tirado Ambrossi, Marcos Arturo (International Journal of Research in Medical Sciences, 2024)
Cervical leiomyosarcomas represent less than 1% of all malignant cervical neoplasms, predominantly affecting perimenopausal women, with an average age of diagnosis at 46 years. This article presents a case involving a 45-year-old female patient admitted to the gynecology department due to pyelonephritis. During initial evaluation, a cervical tumor was incidentally discovered. Histopathological analysis revealed findings consistent with high-grade leiomyosarcoma, not otherwise specified (NOS). The patient underwent surgical intervention, which included sigmoid resection, type III Piver hysterectomy, mechanical side-to-side colorectal anastomosis, appendectomy, placement of JJ stents, and terminal ureterovesical anastomosis. Leiomyosarcomas are associated with a poor prognosis, even when diagnosed at an early stage. The most prevalent symptom is abnormal vaginal bleeding. Surgical intervention is the primary treatment modality for this condition, with the objective of achieving an R0 resection, which entails the complete removal of the tumor.